Kumusta an advocacy campaign that promotes understanding and empathy towards college students with depressive symptoms - Yuvienco, Jose Maria Tristan V.
Psychiatrist Aaron Beck describes depression as an illness caused by distorted perceptions towards the self, environment, and future. It is a global health problem that impairs the lives of millions around the world and tops as one of the most leading causes of disability worldwide. Furthermore, it further contributes to thoughts of suicide. It is a mental health issue that is a challenge to identity, especially for those who are very keen at keeping it hidden. There have been several international efforts and media campaigns launched in order to combat depression. Even online, there is a large amount of support for the illness and suicide prevention. Efforts in the Philippines that combat depression usually comprise of educational tasks, conferences, activities, and media presence. While there have been campaigns on depression, most of these are aimed towards those with the illness. A campaign that primarily focuses to the people that do not know much about depression has yet to be fully explored. Kumusta is an advocacy campaign set in the Philippines that targets those who are confused and misinformed on depression; more specifically, the college students of Metro Manila who haven't experienced the illness. By exploring the concepts of empathy and altruism, the advocacy aims to encourage these values to the target audience through the example of using the everyday word "kumusta", and going beyond it. While the campaign familiarizes the audience with the symptoms, causes, and impacts, of depression, its ultimate goal is to create a caring and understanding view on the illness in hopes to lessen the stigma towards it and mental health as a whole.